Analysis of Amino Acid Composition in the Seeds of Calliandra surinamensis (Pink Powder Puff) - Eze, Patricia; Obielumani, Joy; Okotcha, Evangeline (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2024)
Calliandra surinamensis is a tropical legume shrub that is gradually gaining recognition for its pharmacological and medicinal potential. The amino acid content in the seeds was analyzed and the protein quality was determined. The seeds were found to contain all nine essential amino acids, with varying concentrations. The most abundant essential amino acids were leucine (7.25), methionine (6.04), lysine (4.96), isoleucine (4.90), threonine (2.41), and valine (2.24), while the limiting amino acids where: phenylalanine (0.82) tryptophan (0.27) and histidine (0.02). The non-amino acids found were; Alanine (3.30) Senine (0.84) Proline (0.18), Glutamate (0.05), Aspartate (6.28), Arginine (0.19), Glycine (2.74) and Cysteine (2.73). The protein quality analysis of Calliandra surinamensis seed revealed a Protein Efficiency Ratio (PER) value of 47.7, a high protein digestibility-corrected and amino acid score (PDCAAS) of 0.74, and an Essential Amino Acid Index (EAAI) value of 37.89 due to the restricted makeup in the key amino acids, particularly in phenylalanine, tryptophan, and histidine. The meager chemical score (1.05) indicates that histidine is a severe limiting factor in the protein quality. The EAA / NEAA Ratio was 0.94 suggesting a relatively balanced amino acid profile with a slight emphasis on non-essential amino acids The findings imply that the seeds of Calliandra Suriname are a valuable source of plant-based protein and the protein quality of Calliandra surinamensis seed could be used as a complementary protein source in combination with other proteins that have a more balanced amino acid profile.